Could insoles offload pressure? An evaluation of the effects of arch-supported functional insoles on plantar pressure distribution during race walking - Song, Q.; Xu, K.; Yu, B.; Zhang, C.; Sun, W.; Mao, D. (Research in Sports Medicine, 2015)
This study investigated the effectiveness of functional insoles on plantar pressure distribution during race walking so as to reduce the high plantar pressure and force on race walkers, who tend to suffer from overuse injury. A total of 20 male race walkers aged 21.19 ± 3.66 years and with a mean height of 178.85 ± 14.07 cm were recruited as participants. Each participant completed a race walking with functional or normal insoles. Plantar pressure insoles were used to collect vertical plantar pressure data. A two-way analysis of variance with a mixed design was used to determine the difference between the two conditions. Results showed that the use of functional insoles reduces the peak pressure and the impulse in the metatarsophalangeal joints and heels and thus suggest that functional insoles reduce the overuse injury risks of these parts. The first ground reaction force peak also decreased. This result suggested that functional insoles reduce the risks of foot and leg injuries.